Implementasi Strategi Influencer Marketing Untuk Meningkatkan Brand Awareness pada Produk Indibiz di PT. Telkom Witel Yogyakarta - Imran, Raihan Al; Fadhilla, Hanifa Nur (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of influencer marketing and social media marketing on brand awareness of Indibiz products managed by PT Telkom Witel Yogyakarta. Digital marketing strategies through collaboration with influencers and management of attractive social media content are expected to expand the reach of product information. This study uses a mixed methods approach, namely quantitative and qualitative. The quantitative approach was carried out through a survey method by distributing questionnaires to 100 respondents who are social media users and are aware of Indibiz product promotions. The sampling technique used purposive sampling with the criteria of respondents who actively use social media and have seen the product promotion. Quantitative data were analyzed using multiple linear regression analysis with the help of statistical software. The results of the simultaneous test showed that both independent variables together have a significant effect on brand awareness. In other words, the implementation of a digital marketing strategy through influencer marketing and social media marketing is an effective strategy in increasing brand awareness of Indibiz products.